Tolerancia a estrés de sequía - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
In the 2nd growing season of 1984, reduced no. of materials were used to evaluate the present screening strategy and study mechanisms of drought tolerance. The new materials evaluated included 14 lines from the Brazilian national program, 100 lines from EP/84, and 3 Phaseolus vulgaris x P. acutifolius hybrid lines showing drought tolerance at the U. of California at Davis (USA). The Bean International Drought Yield Trial (BIDYT) and the Bean International Drought Adaptation Nursery (BIDAN) were initiated to evaluate the present screening technique. Preliminary results confirmed that materials selected at CIAT-Palmira would vary greatly in tolerance to drought stress at other sites; particularly noteworthy is that the best lines and var. at CIAT-Palmira and CIAT- Quilichao (San Cristobal 83 and G 5059) had zero yields in CIAT- Popayan, primarily due to poor adaptation. In other trials, the hypothesis which associates drought tolerance with reduced canopy temp., and that this in turn is associated with less reduction in stomatal conductance and water plant potential during periods of peak stress, was tested. These results were attributed to tolerant materials extracting a large amount of soil moisture, presumably through deeper roots. (CIAT)